Changes in marine hot and cold extremes in the China Seas during 1982–2020 - Yan Li; Guoyu Ren; Qingyuan Wang; Lin Mu (Weather and Climate Extremes, 2023)
Extremes in sea surface temperature (SST) have the potential to threaten marine biodiversity, ecosystem functions, and regional services. Using the OISST v2 data, we analyzed the spatial and temporal variability of marine hot and cold events in the China Seas during 1982–2020. Results showed that in majority of the China Seas, frequency of Hot Days (HDs) and Marine heatwaves (MHWs) has significantly increased; severe MHWs (SMHWs) have become more intense. Frequency of Cold Days (CDs) and Marine cold-spells (MCSs) has fallen dramatically; severe MCSs (SMCSs) have become weaker. All of the trend distributions are heterogeneous, with the largest magnitudes along the coast. Long-term temporal analysis revealed that cold extremes (CDs, MCSs, SMCSs) decreased significantly, while hot extremes (HDs, MHWs, SMHWs) increased at a higher confidence level and at a faster rate. Asymmetry characterizes the tendencies of hot and cold extremes. Further study demonstrated that mean SST warming, not SST variability, was the primary driver of trends in both MHW and MCS metrics. MHWs/MCSs related to the anthropogenic or natural forcing increased very rapidly in the post-1998 era.